An Analytical Model for Sb2Se3 Thin‐Film Solar Cells by Considering Current‐Voltage Distortion. Issue 1 (11th November 2022) - Gharibshahian, Iman; Orouji, Ali Asghar; Sharbati, Samaneh
Abstract: Antimony selenide (Sb2 Se3 ) solar cells often demonstrate current–voltage ( J – V ) distortion at low temperature, particularly at reverse bias or under red‐light irradiation. A highly doped p‐type (HDP) thin layer between the buffer and absorber layers is typically supposed to induce the J – V distortion. In this work, an analytical model for the experimental Sb2 Se3 solar cell has been presented to investigate the effect of the HDP layer characteristics on the J – V distortion. This proposed model can also calculate the critical voltage at which the J – V distortion occurs. The results show that the Sb2 Se3 solar cells with the HDP layer have low efficiency when doping concentration and thickness of the HDP layer increase due to a large J – V distortion. This study confirms that the presence of an electron barrier in the conduction band formed by the HDP layer can cause J – V distortion. Hence, the effect of electron barrier height on cell performance based on the derived formulas is investigated. Finally, comparing the simulation and modeling results with variations of the physical and electrical properties of the HDP layer provides a good evaluation for understanding the behavior of Sb2 Se3 solar cells. Abstract : An analytical model for experimental antimony selenide (Sb2 Se3 ) solar cells is proposed to investigate the current–voltage ( J – V ) distortion. For this purpose, a highly doped p‐type (HDP) thin‐film between the CdS buffer and Sb2 Se3 absorber is considered to model J – V distortion. The distortion‐free J – V curves play an essential role in improving the performance of Sb2 Se3 cells.